2002
DOI: 10.1590/s0100-83582002000300019
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de regulador de crescimento na cultura de trigo submetido a diferentes doses de nitrogênio e densidades de plantas

Abstract: Com o objetivo de avaliar os efeitos de um regulador de crescimento no cultivar de trigo IAPAR-53, em diferentes densidades de plantas e submetido a diferentes doses de nitrogênio, instalou-se um experimento na Fazenda-Escola da UEPG em Ponta Grossa-PR, no ano de 1999. O delineamento experimental foi o de blocos ao acaso, em esquema fatorial 2 x 3 x 4, com quatro repetições. Os tratamentos constaram da aplicação de 125 g i.a. ha-1 de trinexapac-ethyl e testemunha sem aplicação, em densidades de 44, 60 e 75 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 1 publication
8
17
1
11
Order By: Relevance
“…A similar trend was found with ethephon and chlormequat chloride (Espindula et al, 2009). The trinexapac-ethyl had longer persistence in inhibiting gibberellin biosynthesis to decrease dry matter production and internode length (Zagonel et al, 2002), and the Chlormequat reduced the amount of active gibberellin (Bode & Wild, 1984). In the present study, the data clearly demonstrated that the crop height was significantly reduced, which was consistent with previous studies (Cailong et al, 2017).…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 91%
“…A similar trend was found with ethephon and chlormequat chloride (Espindula et al, 2009). The trinexapac-ethyl had longer persistence in inhibiting gibberellin biosynthesis to decrease dry matter production and internode length (Zagonel et al, 2002), and the Chlormequat reduced the amount of active gibberellin (Bode & Wild, 1984). In the present study, the data clearly demonstrated that the crop height was significantly reduced, which was consistent with previous studies (Cailong et al, 2017).…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 91%
“…Reduction in SDM was also found for wheat 'IAPAR-53' treated with 125g ha -1 trinexapac-ethyl compared with nontreated plants (ZAGONEL et al, 2002). On the other hand, linear increases in dry weight at higher N rates are related to the lodging reduction promoted by the increase in trinexapac-ethyl rates.…”
Section: Resultsmentioning
confidence: 67%
“…The increase in plant height provided by nitrogen is counterbalanced by the use of the retardant, and the combination of these factors is a strategy to avoid lodging and to achieve higher yields (ZAGONEL et al, 2002). It is necessary however to establish the adequate rates of nitrogen and trinexapacethyl for each cultivar and crop system, because height and architecture as well as physiological answer of wheat cultivars are different.…”
Section: Introductionmentioning
confidence: 99%
“…A redução no crescimento vegetativo de plantas de cultivares de trigo também foi observada por ZAGONEL et al (2002), BERTI et al (2007, ZAGONEL & FERNANDES (2007) e CHAVARRIA et al (2015, sem haver interação entre cultivares e doses, semelhante ao apresentado no presente estudo. A redução da altura de plantas em resposta à aplicação de Etil-trinexapac esteve associada à redução do comprimento dos entrenós do colmo (Tabela 4), sendo que o regulador também afetou o crescimento da bainha da folha bandeira, o que reduziu, assim, a distância entre fonte e dreno.…”
Section: Resultsunclassified
“…Mudanças na morfologia foliar, em termos de espessura e disposição de células, por sua vez, podem resultar em aumento na eficiência fotossintética por unidade de área ou mesmo no controle das trocas gasosas, com efeito direto sobre a fotossíntese e o consumo de água (RICHARDS 2000, THOLEN et al 2012, SONG et al 2013 Reguladores vegetais do grupo dos inibidores da giberelina provocam, entre outros efeitos, a redução do porte (BERTI et al 2007, ZAGONEL & FERNANDES 2007, FIOREZE & RODRIGUES 2014a) e melhorias na arquitetura de plantas (SOUZA & ROSOLEM 2007, FIALHO et al 2009, FIOREZE & RODRIGUES 2014a, CHAVARRIA et al 2015. A redução na altura de plantas tem como benefícios a redução no acamamento, normalmente associados ao uso de maiores doses de nitrogênio e altas densidades de semeadura (ZAGONEL et al 2002).…”
Section: Introductionunclassified